2014
DOI: 10.1007/978-3-319-12283-0_8
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Relationship Between Epilepsy and Headache and the Concept of Ictal Epileptic Headache

Abstract: Key Points-Headache/migraine is often associated with epilepsy in children, as a pre-ictal, ictal, post-ictal or inter-ictal phenomenon.-Epidemiological aspects of the co-morbidity between epilepsy and headache are clearly different in children and adults.-Headache as a symptom, with migraine characteristics and/or tension-type headache characteristics, may be the only clinical ictal manifestation of an epileptic seizure: this condition is now classified as "ictal epileptic headache".-In particular, according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 106 publications
(234 reference statements)
1
19
0
Order By: Relevance
“…Data on perfusion MRI during IEH are not available in the here described cases, as well as in the all few single reported cases [5].…”
Section: "Ictal Epileptic Headache" Conceptmentioning
confidence: 83%
See 4 more Smart Citations
“…Data on perfusion MRI during IEH are not available in the here described cases, as well as in the all few single reported cases [5].…”
Section: "Ictal Epileptic Headache" Conceptmentioning
confidence: 83%
“…1) may be regarded as a possible "subtle" autonomic seizure. In this regard, it has previously been suggested that the IEH phenomenon be classified among "autonomic seizures", as happens for Panayiotopoulos syndrome [2,3,5,8,10]. It has also been suggested [2][3][4][5][11][12][13] that the age-specific lower activation threshold of the autonomic system ("the younger, the more autonomic") may explain the possible isolated headache manifestation during an epileptic seizure, as occurs in autonomic ictal manifestation for Panayiotopoulos syndrome in children [10].…”
Section: Discussion Of the Four Clinical-eeg Casesmentioning
confidence: 93%
See 3 more Smart Citations